Growth and feed efficiency of growing dairy replacement heifers supplemented with rimensin or bovatec - Scheffel, Michael V.; Park, A.; Smith, John F., 1962-; Titgemeyer, Evan C.; Shirley, John E. (Kansas Agricultural Experiment Station and Cooperative Extension Service., 2011)
Ninety Holstein heifers were used to examine the effects of Rumensin® or Bovatec®. Average daily gain and feed efficiency was greater for heifers fed Rumensin® than for heifers fed Bovatec®. Heifers fed Rumensin® consumed more total dry matter per day but slightly less dry matter as a percent of body weight than heifers fed Bovatec®. No differences were observed in body condition score and hip height between dietary treatments. The primary goal of a heifer-feeding program is to obtain a desired rate of gain without fattening at the least possible cost. Results of this study support the use of Rumensin® in diets for growing dairy replacement heifers.
Keywords: Replacement heifers; Rumensin; Bovatec